Insight into the antibacterial activity of lauric arginate against Escherichia coli O157:H7: Membrane disruption and oxidative stress. (1st June 2022) - Zhao, Dianbo; Wang, Shaodan; Hu, Yushan; Liu, Xiao; Tao, Jing; Sagratini, Gianni; Xiang, Qisen
Abstract: Lauric arginate (LAE), an amino acid-based cationic surfactant, has recently attracted great attentions for applications in food preservation due to its antimicrobial properties. This work aimed to unravel the possible antibacterial mechanisms of LAE against Escherichia coli O157:H7. After exposure to LAE at 50 μg/mL for 10 min, the microbial load decreased by 6.25-log units. According to the results of propidium iodide and N-phenyl-1-napthylamine fluorescent staining, LAE severely damaged the cytoplasmic and outer membranes of E. coli O157:H7, leading to a loss of membrane integrity. An increase in DiBAC4 (3) fluorescent intensity was observed in LAE-treated cells, indicating a rapid membrane depolarization. Lipopolysaccharide and peptidoglycan could effectively block LAE-triggered inactivation of E . coli O157:H7 cells, suggesting the binding of LAE with cell membrane components. Moreover, LAE also resulted in an increase in intracellular reactive oxygen species levels and the coadministration of antioxidants (such as ascorbic acid and glutathione) could effectively quench LAE-mediated bacterial inactivation, indicating that oxidative stress was involved in the antibacterial action of LAE. In summary, the antibacterial activity of LAE against bacteria may be associated with a combined action of membrane damage and oxidative stress. This study provides a better understanding of the antibacterial mechanism of LAE. Highlights: Lauric arginate (LAE) caused irreversible damages to cell membranes. Lipopolysaccharide and peptidoglycan reduced the antibacterial activity of LAE. Addition of antioxidants quenched the antibacterial activity of LAE. Membrane damage and oxidative stress are involved in the antibacterial action of LAE.